Post-2015: the international battle against tax fraud and evasion - Christian von Haldenwang; Uwe Kerkow (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
Reports on worldwide tax fraud and illicit global financial flows have been appearing more and more frequently in recent times. In spite of the attention which such revelations attract, however, the international community is still far from an effective system of controls. While it is true that the G20, the G8, the European Union (EU), the Organisation for Economic Co-operation and Development (OECD) and other international organisations are advocating more international cooperation and control in this area, implementation of the related resolutions has proven to be difficult. In its first major report, at the end of May 2013, the United Nations High-Level Panel of Eminent persons on the Post-2015 Development Agenda now proposes that the reduction of illicit flows and tax evasion and the recovery of stolen assets be included in the new global agenda. This initiative deserves support, precisely because many of the poorer countries labour under a disastrous combination of weak national tax and control agencies together with international tax loopholes and regulatory gaps. Large international companies above all use this constellation to shift their profits with the help of internal transfer prices to countries with particularly low tax burdens (so-called tax havens). And it is often much too easy for persons with large private assets to circumvent tax obligations in their own countries. While it is true that no reliable figures are available about the extent to which developing countries are damaged by such behaviour, even the most conservative estimates make it clear that these illicit capital outflows lie on an order of several magnitudes above inflows from official development assistance (ODA), not to mention their negative impacts regarding governance and corruption. Most of these tax havens are found in OECD countries or smaller states and territories which are dependent on them. At the same time, it is the OECD countries which have the market power and public infrastructure to effectively implement controls and plug existing legal tax loopholes. But the major emerging countries too, along with resource-rich developing countries, must be integrated into this effort if actions which have been decided upon are to take effect on a worldwide basis. This topic is thus particularly relevant for a global agenda Beyond Aid . The new agenda should tackle the problem at several points: in order to increase market transparency, reporting and accounting obligations of companies must be expanded and standardised. It is also of major importance to improve international cooperation and the exchange of information between tax authorities. Bilateral accords like those presently in place are not enough for this; rather, multilateral actions by the international community are required. These may be initiated by individual groups of countries, but must then be implemented on a global scale.
Keywords: 330